Inhibition of glutaminase to reverse fibrosis in iatrogenic laryngotracheal stenosis. (6th January 2020) - Tsai, Hsiu‐Wen; Motz, Kevin M.; Ding, Dacheng; Lina, Ioan; Murphy, Michael K.; Benner, Dimitri; Feeley, Michael; Hooper, Jody; Hillel, Alexander T.
Abstract : Objectives/Hypothesis: Glutamine metabolism is a critical energy source for iatrogenic laryngotracheal stenosis (iLTS) scar fibroblasts, and glutaminase (GLS) is an essential enzyme converting glutamine to glutamate. We hypothesize that the GLS‐specific inhibitor BPTES will block glutaminolysis and reduce iLTS scar fibroblast proliferation, collagen deposition, and fibroblast metabolism in vitro. Study Design: Test‐tube Lab Research. Methods: Immunohistochemistry of a cricotracheal resection (n = 1) and a normal airway specimen (n = 1) were assessed for GLS expression. GLS expression was assessed in brush biopsies of subglottic/tracheal fibrosis and normal airway from patients with iLTS (n = 6). Fibroblasts were isolated and cultured from biopsies of subglottic/tracheal fibrosis (n = 6). Fibroblast were treated with BPTES and BPTES + dimethyl α‐ketoglutarate (DMK), an analogue of the downstream product of GLS. Fibroblast proliferation, gene expression, protein production, and metabolism were assessed in all treatment conditions and compared to control. Results: GLS was overexpressed in brush biopsies of iLTS scar specimens ( P = .029) compared to normal controls. In vitro, BPTES inhibited iLTS scar fibroblast proliferation ( P = .007), collagen I (Col I) ( P < .0001), collagen III ( P = .004), and α‐smooth muscle actin ( P = .0025) gene expression and protein production ( P = .031). Metabolic analysis demonstrated that BPTES reduced glycolytic reserve ( P = .007) but had no effects on mitochondrial oxidative phosphorylation. DMK rescued BPTES inhibition of Col I gene expression ( P = .0018) and protein production ( P = .021). Conclusions: GLS is overexpressed in iLTS scar. Blockage of GLS with BPTES significantly inhibits iLTS scar fibroblasts proliferation and function, demonstrating a critical role for GLS in iLTS. Targeting GLS to inhibit glutaminolysis may be a successful strategy to reverse scar formation in the airway. Level of Evidence: NA Laryngoscope, 2020